Two-point Padé approximants to the effective heat conduction coefficient of non-uniform media - May, S. (Archives of Mechanics, 1999)
In [3] the two-point Padé approximants were used to obtain the lower and upper bounds to the effective heat transfer coefficient in the composite with inclusions in the form of densely packed cylinder array. The effective heat transfer coefficient fulfils the Keller symmetry condition, however the asymptotic formula (McPhedran et al.[4]) used to build the approximants does not agree with this condition. By using the Keller symmetry explicitly we transform the asymptotic formula to the symmetric form and obtain better bounds than those in [3].